KORELASI ANTARA KECERDASAN LINGUISTIK DENGAN KOMPETENSI PENGETAHUAN BAHASA INDONESIA SISWA KELAS V SD GUGUS I GUSTI NGURAH RAI DENPASAR BARAT TAHUN PELAJARAN 2017/2018 - Ayu Bintang Christina Dewi (Journal for Lesson and Learning Studies, 2018)
The purpose of this research was to find out the correlation linguistic intelligence with Indonesia language knowledge competencies in Elementary School Gugus I Gusti Ngurah Rai Denpasar Barat Grade V academic period 2017/2018. The type of this research was ex post facto. Research populations were all students Grade V in Elementary School Gugus I Gusti Ngurah Rai Denpasar Barat academic period 2017/2018 which has population over 533 students. Sample was determined by proportional technique random sampling with the level of signification 5% and the number of sample gained from the populations were 218 students. The data retrieved from the recording of language knowledge competencies document Indonesia and linguistic intelligence from essays test by respondents. As the test persyarat is a test of normality distribution data. And the next is testing a hypothesis using correlation analysis product moment. Based on the analysis results we found that  rxycount= 0.448. At a level of signification 5% with n = 218, obtained rxytable= 0.138. Because rxycount> rxytable  = 0.448 > 0.138 it means that H0 that said there is no significant correlation between linguistic intelligence with Indonesia language knowledge competencies in Elementary School Gugus I Gusti Ngurah Rai Denpasar Barat Grade V academic period 2017/2018 was rejected and Ha was accepted. The conclusion was there is correlation between linguistic intelligence with Indonesia language knowledge competencies in Elementary School Gugus I Gusti Ngurah Rai Denpasar Barat Grade V academic period 2017/2018, with positive correlation line, which means the higher the linguistic intelligence will increase with Indonesia language knowledge competencies of students